EVALUATING LANGUAGE SKILLS THROUGH SPORTS ACTIVITIES - Azimova Umirkhon Odilovna (Bright Mind Publishing, 2025)
This article explores the innovative pedagogical approach of using sports activities as a dynamic framework for assessing English language proficiency. Moving beyond traditional, anxiety-inducing testing methods, this approach leverages the engaging and contextualized nature of sports to create authentic assessment environments. The paper details practical strategies for evaluating the four core language skills—listening, speaking, reading, and writing—through activities such as live commentary, rulebook deciphering, coach-style instruction, and post-match reporting. It highlights the significant benefits of this method, including reduced student anxiety, holistic skill integration, and the promotion of soft skills like teamwork and communication. Furthermore, the article addresses potential challenges, such as managing noise levels and ensuring objective assessment, and provides solutions, including the use of tailored rubrics.
Keywords: Language assessment, sports activities, integrated skills, communicative language teaching (CLT), alternative evaluation, performance-based assessment, task-based learning, reducing anxiety.